2014
DOI: 10.1186/1471-2261-14-141
|View full text |Cite
|
Sign up to set email alerts
|

Speckle tracking echocardiography in the diagnosis of early left ventricular systolic dysfunction in type II diabetic mice

Abstract: AbstractsBackgroundThe leptin receptor-deficient db/db mouse is a well-established type II diabetes animal model used to investigate diabetic cardiomyopathy. Previous reports have documented diabetic cardiomyopathy is accompanied by cardiac structural and functional abnormalities. To better elucidate early or subtle changes in cardiac performance in db/db mice, we used speckle tracking echocardiography to assess systolic myocardial strain in vivo with diabetic db/db mice in order to study early changes of left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…3 Two-dimensional strain has been recently presented as a strong predictor of different cardiac pathologies including CAD. 4,5 Since the use of ultrasound strain in identifying the acutely ischemic myocardium was reported in 2003 6 the role of two-dimensional strain in the diagnoses of CAD at rest has been investigated in a number of studies involving different patients' groups like diabetic patients or those with suspected new onset non-ST segment elevation acute coronary syndrome. 7,8 It was not until recently that the incremental value of twodimensional strain to DSE has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…3 Two-dimensional strain has been recently presented as a strong predictor of different cardiac pathologies including CAD. 4,5 Since the use of ultrasound strain in identifying the acutely ischemic myocardium was reported in 2003 6 the role of two-dimensional strain in the diagnoses of CAD at rest has been investigated in a number of studies involving different patients' groups like diabetic patients or those with suspected new onset non-ST segment elevation acute coronary syndrome. 7,8 It was not until recently that the incremental value of twodimensional strain to DSE has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the association between early myocardial dysfunction and abnormal interstitial depositions of collagen and amyloid material has been elucidated in several animal models of HFpEF. 47,48 Similarly, in a rat model of chronic hypertension, it was recently noticed that progressive disruption of T-tubule and defects in calcium cycling started at an early stage and were associated with progressive subclinical reductions in systolic and diastolic myocardial mechanics. These changes preceded the occurrence of clinical symptoms and development of cardiac fibrosis, which was associated with the fall in LVEF.…”
Section: Myocardial Mechanics and Molecular Mechanisms Of Hfmentioning
confidence: 99%
“…36 We now extend prior findings to also highlight a role for leptin in relation to LV systolic mechanics in humans, which corroborates prior findings in leptin-receptor deficient animal models. 37 It is important to note that data linking circulating leptin concentrations to clinical outcomes in population-based studies have shown conflicting results, with some studies suggesting higher risk and others a null or even protective effect. 38-40 …”
Section: Discussionmentioning
confidence: 99%